Perfil dos pacientes coinfectados pelos vírus das Hepatites B ou C e da Imunodeficiência Adquirida em Sergipe - Reis, André Augusto de Vasconcelos Ouro (2017)
Introduction: Coinfection with the human deficiency virus and B and C viruses causes greater morbidity and mortality in its carriers. Objective: To evaluate the epidemiological, serological and treatment profile of coinfected patients in Sergipe. Methods: This was a cross-sectional retrospective study based on data obtained from the medical records of patients infected with HIV and HBV and / or HCV virus treated at HU and CEMAR from 2006 to 2016. Descriptive statistics were performed and quantitative data and qualitative variables were represented by mean, median and absolute and relative frequencies. Results: A total of 65 coinfected patients were found, most of them men (75.4%), with a mean age of 47.9 ± 8.6 years. All patients were infected with HIV, 40 (61.5%) had hepatitis C, 6 (15.0%) had prior contact with HBV and 2 (5.0%) had HBV immunity through contact with HBV. While 17 (26.2%) patients had chronic hepatitis B, 7 (10.8%) had only previous contact with HBV and 3 (4.6%) had triple infection. The main risk factor was the practice of unsafe sex (75.4%). Among the complications, 16 (24.6%) developed hepatic fibrosis, 2 (3.1%) had hepatocarcinoma and 1 (1.5%) died. There were no HIV treatment for 6 (9.2%) patients. For Hepatitis C, 17 (29.2%) underwent treatment with pegylated interferon and Ribavirin, 6 of which (35.3%) started treatment with sofosbuvir. Conclusions: HCV coinfection is greater than with HBV virus, has similar risk factors and worsens the patient's prognosis.